MAKNA DENOTATIF DAN KONOTATIF PADA ARTIKEL POS JAKARTA - Resty Wahyuni; Siti Fatma Sari (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study deals with the analysis of Denotative and Connotative meaning on the Jakarta Post article. The objectives of the study was to find out the types of meaning used in Jakarta Post Article, to find out the types of the dominant meaning used on Jakarta post article and to explain the meaning of the most dominant types used on Jakarta Post article.This study was conducted by applying descriptive qualitative method. The data were taken from Jakarta Post Article, which published from October 2017, November 2017, and December 2017. The finding showed that total of Denotative meaning is 88 (63,3%) and total of Connotative meaning is 51 (36,6%) that is found from 6 articles. Its hope that the result of this study will be useful to everyone who wants to study meaning Jakarta Post Article.Keywords: Denotative Meaning, Connotative Meaning, Descriptive Qualitative Design.